Morphological relationships, growth patterns and some aspects of reproductive biology of Sind Danio Devario devario (Hamilton 1822) - Md Mokaddes Alam; Humayon Ahmmed; Shihad Shahoriare Sujan; Anika Tabassum Sama; Md Rezoanul Haque; Md. Rashidul Islam (Journal of Fisheries, 2023)
This study examined the morphological relationships, growth population factors and reproductive biology of Devario devario collected from the Atrai River of Dinajpur, Bangladesh, for sustainable management and conservation aspects. The length-weight relationships (LWRs) commonly indicated the isometric growth. The Fulton’s condition factor (CFf) and relative body weight (BWr) varied across sexes. A positive correlation was found in length-length relationships (LLRs); among total length (TL), standard length, head length and fork length. The asymptotic lengths were 7.5, 7.2 and 7.5 cm, with growth rates of 0.78‒1.8, 0.6‒3.4 and 1.8‒3.6 year–1 while total mortality was 1.22‒3.06, 0.97‒7.07 and 3.70‒6.09 year–1; fishing mortality was –0.87 to –1.04, –0.97 to 1.09 and –0.05 to –0.23 year–1; natural mortality was 2.26–3.93, 1.94–5.98 and 3.93–6.14 year–1 for female, male and combined sexes respectively. The highest probability of capture (L50) was 5.74‒6.15 cm. The gonado-somatic index ranged from 32.75±1.82 to 44.12±2.73, with a peak in April to May. Fecundity was recorded from 3253±289 to 4831±342, with a significant correlation among TL, BW, gonad length (GL) and gonad weight (GW). These initial findings on D. devario will serve as the basis for future research and management.